Efek Financial Management Behavior, Self Efficacy, Herding Terhadap Keputusan Investasi Generasi Z (Effects of Financial Management Behavior, Self-Efficacy, Herding on Generation Z Investment Decisions) - Hidayat, Fikri; Siregar, Sandra Rosalie; Nugroho, Arif Widodo (STIE Malangkucecwara, 2023)
This study was conducted to better understand the impact of financial management behavior, self-efficacy, and herding on the investment decisions of Generation Z. Those born between the years of 1997 and 2010, sometimes known as